Last visit was: 24 Jul 2024, 20:15 It is currently 24 Jul 2024, 20:15
Close
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Close
Request Expert Reply
Confirm Cancel
SORT BY:
Kudos
Tags:
Difficulty: Sub 505 Level,   Algebra,                                       
Show Tags
Hide Tags
User avatar
Manager
Manager
Joined: 02 Dec 2012
Posts: 172
Own Kudos [?]: 24554 [102]
Given Kudos: 29
Send PM
Most Helpful Reply
Math Expert
Joined: 02 Sep 2009
Posts: 94609
Own Kudos [?]: 643671 [36]
Given Kudos: 86737
Send PM
Math Expert
Joined: 02 Sep 2009
Posts: 94609
Own Kudos [?]: 643671 [9]
Given Kudos: 86737
Send PM
General Discussion
Math Expert
Joined: 02 Sep 2009
Posts: 94609
Own Kudos [?]: 643671 [5]
Given Kudos: 86737
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
3
Kudos
2
Bookmarks
Expert Reply
selfishmofo wrote:
Bunuel wrote:
Walkabout wrote:
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3
(B) -1/2
(C) 0
(D) 1/2
(E) 3/2


x(2x + 1) = 0 --> x=0 OR x=-1/2;
(x + 1/2)(2x - 3) = 0 --> x=-1/2 OR x=3/2.

x=-1/2 satisfies both equations.

Answer: B.


Can you show how you manipulated both of the equations to get to zero, and to -1/2, and 3/2, thanks.


When a product of two multiples is 0, it means that either of the multiples (or both) is 0.

\(x(2x + 1) = 0\) --> \(x=0\) or \(2x+1=0\) (\(x=-\frac{1}{2}\)).

\((x + \frac{1}{2})(2x - 3) = 0\) --> \(x+\frac{1}{2}=0\) (\(x=-\frac{1}{2}\)) or \(2x - 3=0\) (\(x=\frac{3}{2}\)).

Hope it's clear.
Tutor
Joined: 17 Jul 2019
Posts: 1304
Own Kudos [?]: 1749 [3]
Given Kudos: 66
Location: Canada
GMAT 1: 780 Q51 V45
GMAT 2: 780 Q50 V47
GMAT 3: 770 Q50 V45
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
1
Kudos
2
Bookmarks
Expert Reply
Video solution from Quant Reasoning:
Subscribe for more: https://www.youtube.com/QuantReasoning? ... irmation=1
Target Test Prep Representative
Joined: 14 Oct 2015
Status:Founder & CEO
Affiliations: Target Test Prep
Posts: 19199
Own Kudos [?]: 22718 [2]
Given Kudos: 286
Location: United States (CA)
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
1
Kudos
1
Bookmarks
Expert Reply
Walkabout wrote:
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3
(B) -1/2
(C) 0
(D) 1/2
(E) 3/2


To solve we will use the zero product property. The zero product property states that if the product of two quantities is equal to 0, then at least one of the quantities has to be equal to 0. That is, if a  b = 0, then either a = 0 or b = 0. Of course, both a and b can be 0 at the same time. The point is that at least one of them has to be 0.

Let’s start determining the value(s) of x in the equation x(2x + 1) = 0

If x(2x + 1) = 0, we know:

x = 0

OR

2x + 1 = 0

2x = -1

x = -1/2

Thus, x = 0 or x = -1/2

Let’s now determine the value(s) of x in the second equation (x + 1/2)(2x - 3) = 0

(x + 1/2)(2x - 3) = 0, we know:

(x + 1/2) = 0

x = -1/2

OR

(2x - 3) = 0

2x = 3

x = 3/2

Thus, x = -1/2 or x = 3/2

Because we need to determine a value for x in both equations, the answer is x = -1/2.

The answer is B.
VP
VP
Joined: 20 Jul 2017
Posts: 1297
Own Kudos [?]: 3586 [2]
Given Kudos: 162
Location: India
Concentration: Entrepreneurship, Marketing
GMAT 1: 690 Q51 V30
WE:Education (Education)
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
1
Kudos
1
Bookmarks
LeenaSai wrote:
Hi all ,

I ended up by solving the two quadratic equations simultaneously to find the value of x instead of solving one by one for the value of x .

Posted from my mobile device


LeenaSai

You don’t need to solve for quadratic here. It’s already given in solved form.

If a quadratic equation after factorisation would look like (x - a)(x - b) = 0
—> x - a = 0 or x - b = 0
—> x = a or b

Given 1st quadratic equation,
x(2x + 1) = 0
—> x = 0 or 2x + 1 = 0
—> x = 0 or -1/2

and 2nd quadratic equation,
(x + 1/2)(2x - 3) = 0
—> x + 1/2 = 0 or 2x - 3 = 0
—> x = -1/2 or x = 3/2

Combining 1st and 2nd equation, we get common value of x as -1/2

So, Option B
User avatar
Manager
Manager
Joined: 15 Aug 2013
Posts: 176
Own Kudos [?]: 340 [1]
Given Kudos: 23
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
1
Kudos
Bunuel wrote:
Walkabout wrote:
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3
(B) -1/2
(C) 0
(D) 1/2
(E) 3/2


x(2x + 1) = 0 --> x=0 OR x=-1/2;
(x + 1/2)(2x - 3) = 0 --> x=-1/2 OR x=3/2.

x=-1/2 satisfies both equations.

Answer: B.


This makes complete sense, although, I ran into trouble when I tried to FOIL the second equation and ended up with x^2-x-3/4=0 and from that point forward, I was completely stumped. Why is that method wrong?

I notice that I get confused on that front quite a bit - FOIL'ing vs. just setting both parenthesis to 0?

EDIT: As I was doing other problems, I ran into DS 67, Pg 180 of OG 13. The equation there is n(n+1) = 6, if I use the same methodology outlined above, the two solutions I get are n=6 and n=5. That is obviously wrong and I should've opted to FOIL in the above case. Hence my confusion -- why is it that in some situations I need to FOIL and in some other situations, I need to just equate the left to the right side WITHOUT foiling?
User avatar
Intern
Intern
Joined: 14 May 2014
Posts: 35
Own Kudos [?]: 161 [1]
Given Kudos: 1
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
1
Bookmarks
Multiplication of any number with 0 gives 0 ..

When product of two or more expressions is zero, then any expression or product of combination of expressions can be 0.

Here,
x(2x+1) = 0
here product of x and 2x+1 equals 0 => either x = 0 or 2x+1 = 0 or both

hence x=0 or -1/2 will satisfy the first equation.

(x+1/2)(2x-3) = 0
here product of x+1/2 and 2x-3 equals 0=> either x+1/2 = 0 or 2x-3 = 0 or both

hence x = -1/2 or 3/2 will satisfy the second equation.
-1/2 is common in both sets hence x= -1/2 will satisfy both equations.

Hence answer is B.
SVP
SVP
Joined: 20 Mar 2014
Posts: 2356
Own Kudos [?]: 3650 [1]
Given Kudos: 816
Concentration: Finance, Strategy
GMAT 1: 750 Q49 V44
GPA: 3.7
WE:Engineering (Aerospace and Defense)
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
1
Bookmarks
tigrr49 wrote:
Bunuel wrote:
Walkabout wrote:
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3
(B) -1/2
(C) 0
(D) 1/2
(E) 3/2


\(x(2x + 1) = 0\) --> \(x=0\) OR \(x=-\frac{1}{2}\);

\((x + \frac{1}{2})(2x - 3) = 0\) --> \(x=-\frac{1}{2}\) OR \(x=\frac{3}{2}\).

\(x=-\frac{1}{2}\) satisfies both equations.

Answer: B.




Should we apply the same logic to data sufficiency questions if we are asked to find the value of x and given each quadratic as one of the statements? Thus, statement 1 and statement 2 would each be insufficient but combining together they are sufficient (i.e. the answer is C) due to one shared solution for both quadratics/statements?


Technically, yes, C would be your answer in a similarly worded DS problem. But beware that not all quadratic equations give you 2 distinct values.

Lets say, statement 1 gave you:

\(x^2+2x+1\) = 0 , this is in fact \((x+1)^2\) ---> \((x+1)^2 = 0\)---> \(x = -1\) .

So you get ONLY 1 value and thus this statement will be sufficient on its own. Thus, in DS questions, you should be making sure that you actually are getting 2 distinct values.
GMAT Club Legend
GMAT Club Legend
Joined: 19 Dec 2014
Status:GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Posts: 21835
Own Kudos [?]: 11799 [1]
Given Kudos: 450
Location: United States (CA)
GMAT 1: 800 Q51 V49
GRE 1: Q170 V170
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
1
Kudos
Expert Reply
Hi All,

This question gives us a couple of Quadratic equations that have already been factored:

(X)(2X + 1) = 0 and (X + ½)(2X – 3) = 0

We’re asked when X equals. This is a standard mid-level Algebra prompt that has already done half the work for us, so we just need to calculate the two values of X in each equation and find the one answer that shows up in BOTH equations.

With (X)(2X + 1) = 0

X = 0 and X = -1/2 are the two solutions

With (X + ½)(2X – 3) = 0

X = -1/2 and X = 3/2 are the two solutions

Based on these results, the answer that shows up in BOTH is…

Final Answer:

GMAT Assassins aren’t born, they’re made,
Rich
avatar
Intern
Intern
Joined: 11 Aug 2013
Posts: 22
Own Kudos [?]: 24 [0]
Given Kudos: 9
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
Bunuel wrote:
Walkabout wrote:
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3
(B) -1/2
(C) 0
(D) 1/2
(E) 3/2


x(2x + 1) = 0 --> x=0 OR x=-1/2;
(x + 1/2)(2x - 3) = 0 --> x=-1/2 OR x=3/2.

x=-1/2 satisfies both equations.

Answer: B.


Can you show how you manipulated both of the equations to get to zero, and to -1/2, and 3/2, thanks.
avatar
SVP
SVP
Joined: 27 Dec 2012
Status:The Best Or Nothing
Posts: 1558
Own Kudos [?]: 7303 [0]
Given Kudos: 193
Location: India
Concentration: General Management, Technology
WE:Information Technology (Computer Software)
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
\((x + \frac{1}{2})(2x - 3) = 0\)

Multiply both sides by 2

(2x+1)(2x-3) = 0............ (1)

The other equation

x (2x+1) = 0 ............. (2)

With RHS 0 of both the equations, LHS has 2x+1 in common

Equating to 0

x \(= -\frac{1}{2}\)

Answer = B
User avatar
Manager
Manager
Joined: 15 Aug 2013
Posts: 176
Own Kudos [?]: 340 [0]
Given Kudos: 23
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
russ9 wrote:
Bunuel wrote:

x(2x + 1) = 0 --> x=0 OR x=-1/2;
(x + 1/2)(2x - 3) = 0 --> x=-1/2 OR x=3/2.

x=-1/2 satisfies both equations.

Answer: B.


This makes complete sense, although, I ran into trouble when I tried to FOIL the second equation and ended up with x^2-x-3/4=0 and from that point forward, I was completely stumped. Why is that method wrong?

I notice that I get confused on that front quite a bit - FOIL'ing vs. just setting both parenthesis to 0?

EDIT: As I was doing other problems, I ran into DS 67, Pg 180 of OG 13. The equation there is n(n+1) = 6, if I use the same methodology outlined above, the two solutions I get are n=6 and n=5. That is obviously wrong and I should've opted to FOIL in the above case. Hence my confusion -- why is it that in some situations I need to FOIL and in some other situations, I need to just equate the left to the right side WITHOUT foiling?


Hi Bunuel,

Still a little confused about the above question. I ran into countless more errors over the past few days -- cause was the same reason mentioned above. Would greatly appreciate some clarification.

Thanks!
avatar
Intern
Intern
Joined: 18 May 2014
Posts: 2
Own Kudos [?]: 1 [0]
Given Kudos: 2
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
Bunuel wrote:
Walkabout wrote:
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3
(B) -1/2
(C) 0
(D) 1/2
(E) 3/2


\(x(2x + 1) = 0\) --> \(x=0\) OR \(x=-\frac{1}{2}\);

\((x + \frac{1}{2})(2x - 3) = 0\) --> \(x=-\frac{1}{2}\) OR \(x=\frac{3}{2}\).

\(x=-\frac{1}{2}\) satisfies both equations.

Answer: B.




Should we apply the same logic to data sufficiency questions if we are asked to find the value of x and given each quadratic as one of the statements? Thus, statement 1 and statement 2 would each be insufficient but combining together they are sufficient (i.e. the answer is C) due to one shared solution for both quadratics/statements?
User avatar
Intern
Intern
Joined: 06 Jun 2014
Posts: 35
Own Kudos [?]: 82 [0]
Given Kudos: 105
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
I do understant the Method given by Bunuel, but I tried to look for different solution and came to the following :

Equation 1 : x(2x+1)=0 => 2x^2 +x=0 => 2x^2=-x

Equation 2: ( X+1/2)(2x+3) after FOIL => 2x^2 -2x-3/2 , and here I replaced 2x^2 with -x from the first equation and got
-x-2x-3/2=o => -3x=3/2 => x=-1/2

I would like kindly ask Bunuel or other experts if this is also a correct solution?
SVP
SVP
Joined: 20 Mar 2014
Posts: 2356
Own Kudos [?]: 3650 [0]
Given Kudos: 816
Concentration: Finance, Strategy
GMAT 1: 750 Q49 V44
GPA: 3.7
WE:Engineering (Aerospace and Defense)
Send PM
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
kzivrev wrote:
I do understant the Method given by Bunuel, but I tried to look for different solution and came to the following :

Equation 1 : x(2x+1)=0 => 2x^2 +x=0 => 2x^2=-x

Equation 2: ( X+1/2)(2x+3) after FOIL => 2x^2 -2x-3/2 , and here I replaced 2x^2 with -x from the first equation and got
-x-2x-3/2=o => -3x=3/2 => x=-1/2

I would like kindly ask Bunuel or other experts if this is also a correct solution?


Yes, this is a correct method but a bit more time consuming method. In GMAT, you must do proper time management and not just solve the questions correctly.

When you are given a*b =0 ---> 3 cases possible

1. a=0 and b \(neq\) 0

2. b=0 and a \(neq\) 0

3. a=b=0

When you are directly given x(2x + 1) = 0 --> either x=0 or 2x+1 =0 --> x=-0.5.

Similarly from the second equation, (x + 1/2)(2x - 3) = 0 ---> either x+0.5 =0 --> x=0 or 2x-3 =0 -->x=1.5.

From these 2 sets of solutions, you see that x=-0.5 is the common solution and is hence the value of x asked in the question.

Hope this helps.
Manager
Manager
Joined: 07 Feb 2017
Posts: 129
Own Kudos [?]: 51 [0]
Given Kudos: 11
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
x = 0 or x = -1/2
and
x = -1/2 or x = 3/2

Answer B
Manager
Manager
Joined: 31 Mar 2019
Posts: 87
Own Kudos [?]: 57 [0]
Given Kudos: 105
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
Hi all ,

I ended up by solving the two quadratic equations simultaneously to find the value of x instead of solving one by one for the value of x .

Posted from my mobile device
GMAT Club Legend
GMAT Club Legend
Joined: 03 Jun 2019
Posts: 5312
Own Kudos [?]: 4250 [0]
Given Kudos: 161
Location: India
GMAT 1: 690 Q50 V34
WE:Engineering (Transportation)
Send PM
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
Walkabout wrote:
If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3
(B) -1/2
(C) 0
(D) 1/2
(E) 3/2


x(2x+1)=0
x=0 or -1/2

(x+1/2)(2x-3)=0
x=-1/2 or 3/2

x=-1/2 is common to both equations

IMO B

Posted from my mobile device
GMAT Club Bot
Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]
 1   2   
Moderator:
Math Expert
94609 posts